Enhancing the Analytical Abilities of Fifth Grade Students at SDN 1 Pasirgintung CikulurThrough the Application of the Picture and Student Learning Model - Nurjanah, Siti (AIM: Journal of Islamic Education Management, 2024)
This research aims to enhance the analytical skills of fifth-grade students at SD Pasirgintung, Lebak Banten, on the subject of the Struggle Against Dutch and Japanese Colonization. The study design utilizes Classroom Action Research developed by Kemmis & McTaggart, consisting of four stages: planning, acting, observing, and reflecting. The research was conducted over two cycles, with each cycle comprising two meetings. The subjects were 28 fifth-grade students at SD Pasirgintung, Lebak Banten. Data collected included information on the results and processes of learning through the implementation of the Picture and Student Active model on the aforementioned topic. Data collection techniques employed were observation, tests, and questionnaires. The findings indicate that the application of the Picture and Student Active model significantly improved the students' analytical abilities. This conclusion is based on the achievement of average scores and completion percentages. Observations of the learning process using the Picture and Student Active model showed that students were able to analyze the background of Dutch and Japanese colonization in Indonesia. Based on the results of the analytical ability tests, the average score achieved in the first cycle was 76.16 with a completion percentage of 52.51%. In the second cycle, the average score was 81.75 with a completion percentage of 83.97%. Therefore, the application of the Picture and Student Active model effectively enhanced the students' analytical skills on the subject of the Struggle Against Dutch and Japanese Colonization